The Pentecostal Experience in the Lower Cross River Region: Illumination or a Quest for Freedom 1960-2015 - Ubong James Essien; James Aboh (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
Any study of the spread of Christian churches in the Lower Cross River Region would indicate that there has been a gradual push towards Pentecostalism and Evangelical Christianity. A number of factors are responsible for this. The Reformation, which began in Germany between 1517 and 1600 and spread to the rest of the world, was a shift from traditional Christian doctrine and practices. Through deep study of the Bible, Luther advocated the end of a number of ancient Christian practices like penance on the basis that vital parts of scripture were being ignored. The information was hinged on the revelation from Habakkuk 2 vs. 4 that the just shall live by faith. It has, however, been observed that a number of churches that emerged from the reformation, like the Lutheran, Methodist, Apostolic, Presbyterian, and Assemblies of God, have all gravitated steeply towards traditional Catholic practices. This has led to a discourse in Christian circles, with the argument being that the old way could be better. Preachers of Pentecostalism have often been referred to as “Pente-rascals,” indicating that they have used the Pentecostal movement as an excuse for rascality. Evidence abounds to support this assertion, ranging from diversion of church funds, outright embezzlement of church funds, seduction by the clergy, false doctrine, and an opulent lifestyle. These practices have become common place in Pentecostal circles to the extent that a number of the uninformed see Christian ministry as a profession for lazy people who do not want to work. The flamboyant lifestyles of ministers of the gospel, their unguarded utterances, and tendency to manipulate and extort, which is in stark contrast to the gospel which Jesus preached, lends credence to this. Hence, this tends to support the argument that the push towards Pentecostalism is driven by a desire for freedom and liberty. These are the issues that this article will seek to address. The article will make use of primary and secondary sources.